Biogas Engine Emissions: Standards and On-Site Measurements. (September 2017) - Benato, Alberto; Macor, Alarico; Rossetti, Antonio
Abstract: The European Union, with 60% of the total global production of biogas, is the world leader. In 2012, the percentage of electrical energy produced by biogas was 6% of the EU-28 electricity generated through renewable sources while, in 2013, the almost 830 biogas units produced 7448 GWh which corresponds to 14% of EU-28 gross electricity production. Germany, U.K. and Italy are the main EU biogas producers with over 78% of the 2013 primary energy production. Electricity production is the main biogas energy recovery form because the engine cooling water is used to maintain the digester required temperature while energy crops and manure are the most used organic matters. Spark-ignition engines with a rated power of 1MWel in which the filtered biogas is burned to produce work is the widely-adopted technology. With the aim of analyzing the emissions of a real biogas engine, in the present work, the authors firstly present an overview of the Italian biogas sector and the most used conversion technologies. Then, the standards which regulate the biogas plant emissions and the emissions data acquired during a one-year monitoring activity on 10 biogas plants are presented and discussed with the aim of assessing the biogas units' real emissions.